Analysis of Peak Ground Acceleration (PGA) and Modified Mercalli Intensity (MMI) Scale using PSHA Method in Lampung Province - Yahya, Muhammad Harun; Ashari, Almaida Enggar; Syahbana, Arifan Jaya; Kuntjoro, Yanif Dwi; Luthfin, Ahmad (Universitas Negeri Yogyakarta, 2024)
Earthquakes are inevitable natural disasters that are challenging to predict, yet effective mitigation is crucial. Lampung Province, located in Indonesia, faces significant tectonic activity due to the Sumatra Fault System (SFS) and the subduction of the Indo-Australian and Eurasian plates. Its strategic location as the gateway to Sumatra Island further underscores the importance of understanding earthquake hazards in the region. This study analyzes earthquake risks in Lampung Province using a micro-scale approach that integrates Peak Ground Acceleration (PGA) and Modified Mercalli Intensity (MMI) values through the PSHA method. The PSHA method identifies earthquake microzonations and generates PGA values that are then converted to the MMI scale to determine the intensity of earthquake strength. The mapping of Lampung Province identified five zones with different levels of earthquake hazard, ranging from VII to XI MMI with varying PGA values. The first zone, on the VII MMI scale, has a PGA ranging from 0.20 to 0.25g. The second zone, in the VIII MMI scale category with PGA ranging from 0.20 to 0.40g. The third zone, falls within the IX MMI scale category with PGA ranging from 0.40 to 0.70 g. The fourth zone is categorized as X MMI scale with PGA values ranging from 0.70 to 1.00g. The fifth zone, has a scale of XI MMI with a range of PGA values between 1.00 and 2.50 g. Areas with higher PGA and MMI scales indicate a greater potential for severe damage, highlighting the need for targeted mitigation strategies in high-risk zones. These findings provide a foundation for disaster preparedness and urban planning in Lampung Province.